Chemotherapy as a risk factor for caries and gingivitis in children with acute lymphoblastic leukemia: A retrospective cohort study. Issue 4 (20th December 2021) - Shayani, Anis; Aravena, Pedro Christian; Rodríguez‐Salinas, Carolina; Escobar‐Silva, Pamela; Diocares‐Monsálvez, Yandolín; Angulo‐Gutiérrez, Carolina; Rivera, César
Abstract: Background: Dental and oral anomalies are among the most common long‐term side effects of childhood cancer therapy. Aim: To evaluate chemotherapy as a risk factor for caries lesions and gingivitis in children with acute lymphoblastic leukemia (ALL) treated with the ALL IC‐BFM 2009 chemotherapy protocol. Design: A retrospective cohort study was designed. Clinical records of 23 paediatric patients with ALL exposed to chemotherapy in the Regional Hospital in Valdivia, Chile, and 46 unexposed patients assessed every 3 months for 24 months were analyzed. The data on gender, age, index of the number of decayed, missing, or filled teeth, and the presence of gingivitis were recorded (Mann–Whitney U test and logistic regression analysis, p  ≤ .05). Results: A significantly greater frequency of gingivitis (69.57%; p  < .002) and a mean of new caries lesions were observed in children treated with chemotherapy than in the unexposed children ( p  < .01). The chemotherapy protocol presented a relative risk of 2.15 (95% CI = 1.22 ‐ 2.66; p  = .01) for new caries lesions and 2.29 (95% CI = 1.76 ‐ 3.82; p  = .002) for gingivitis. Conclusion: The ALL IC‐BFM 2009 chemotherapy protocol in patients with ALL is a risk factor for new caries lesions and gingivitis.